ASSOCIATION OF C-REACTIVE PROTEIN WITH HYPERLIPIDEMIA IN PATIENTS WITH POLYCYSTIC OVARIAN SYNDROME IN KHYBER PAKHTUNKHWA - Sobia Ali,; Hajira Ishaq,; Naheed Khattak,; Sadaf Durrani,; Ubaid ur Rehman,; Romana Irshad,; Mudassir Ahmad Khan, (Journal of Ayub Medical College Abbottabad, 2022)
Background: It has been unknown whether there exist any relations of C-Reactive Protein (CRP) level with hyperlipidaemia in polycystic ovarian syndromes patients. To determine Association of CRP with Hyperlipidaemia in patients with polycystic ovarian syndrome. Method: This was a cross sectional descriptive study conducted among 50 each polycystic ovarian syndrome and normal women. After taking a written consent from participants predesigned questionnaire was filled including information regarding demography and medical history. A 3 to 5 ml blood was taken from patients and controls and transferred to laboratory for determination of CRP level and lipid profile. The test results were collected, compiled, entered and analyzed using SPSS Version 20 for determination of any kind of association of CRP with Hyperlipidaemia in patients with polycystic ovarian syndrome. Results: The mean age of study participants was 29.72±4.00 for cases and 29.04±3.99 for control. The cases and control were with the same age range, however there was a significant difference p=0.00 in BMI of the cases and control. There was no significant association observed between CRP and lipid profile parameters among polycystic ovarian syndrome patients. Conclusion: There exist no association between increasing CRP level and hyperlipidaemia in polycystic ovarian syndrome patients however CRP and lipid profile parameters showed high values among these patients.